2002
DOI: 10.1002/hed.10207
|View full text |Cite
|
Sign up to set email alerts
|

Complications in transoral CO2 laser surgery for carcinoma of the larynx and hypopharynx

Abstract: Complications after transoral laser surgery of larynx and hypopharynx carcinomas are relatively frequent (18.9%), but serious sequelae and mortality rate are low. Complications are associated with tumor extension, limited surgical experience, and diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
93
1
6

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 124 publications
(109 citation statements)
references
References 21 publications
9
93
1
6
Order By: Relevance
“…One study focusing on the learning curve for transoral laser supraglottic laryngectomy found a significant correlation between surgical experience and compli cations. 12 In our previous study, TORS supraglottic laryngectomy in a canine model was found to have a short learning curve, and the time needed to com plete the procedure was less than 30 minutes. 4 The average time for the TORS supraglottic partial lar yngectomy in this study was 120 minutes, and al though this is longer than in the canine model, it is the authors' impression that the technical advan tages of the robotic system have contributed to the shortening of the learning curve in TORS supraglot tic partial laryngectomy.…”
Section: Discussionmentioning
confidence: 92%
“…One study focusing on the learning curve for transoral laser supraglottic laryngectomy found a significant correlation between surgical experience and compli cations. 12 In our previous study, TORS supraglottic laryngectomy in a canine model was found to have a short learning curve, and the time needed to com plete the procedure was less than 30 minutes. 4 The average time for the TORS supraglottic partial lar yngectomy in this study was 120 minutes, and al though this is longer than in the canine model, it is the authors' impression that the technical advan tages of the robotic system have contributed to the shortening of the learning curve in TORS supraglot tic partial laryngectomy.…”
Section: Discussionmentioning
confidence: 92%
“…Bernal et al [4] classifies postoperative complications in minors, when they are self-limited, can be managed with medical treatment and leave no sequelae, and mayors, when they required surgical resolution, intensive care or leave sequelae that may require a tracheostomy or gastrostomy feeding tube definitively [4]. Steiner & Ambrosch [5] had no intraoperative complications for the CO 2 laser technique, in 704 patients treated for tumors of the larynx and hypopharynx.…”
Section: Discussionmentioning
confidence: 99%
“…Other articles [4,8] mention an incidence of 0.4 to 8% for postoperative bleeding. In a multicenter study of transoral treatment in advanced tumors [9], it is reported, a postoperative bleeding of 6% and mortality of 5 % within 30 days after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 While the incidence of cervical emphysema caused by transoral CO 2 laser surgery for carcinoma of the larynx and pharynx is reported to be in the range of 1.1% (3/275 cases) to 7.3% (4/55 cases), 15,16 the incidence of emphysema caused by dental laser treatment is lower.…”
Section: Discussionmentioning
confidence: 99%